Trajectory of inhaled cadmium ultrafine particles in smokers - Einat Fireman Klein; Ilan Klein; Omer Ephrat; Yoram Dekel; Aharon Kessel; Yochai Adir (BMJ Open Respiratory Research)
Introduction Tobacco smoking is a significant source of cadmium exposure among smokers. Most of inhaled heavy metals, including cadmium, are attached to ultrafine particles (UFPs) surface. A low inhaled UFP content in exhaled breath condensate reflects a high inflammatory status of airways. Increased respiratory epithelial permeability and translocation to the circulation is the proposed mechanism. UFP recovered from smokers’ airways have high levels of cadmium compared with the airways of non-smokers.Methods Urine was collected from 22 smokers subjects and 43 non-smokers. Samples were analysed for UFP and cadmium content. UFP were measured in urine samples by means of the NanoSight LM20 system (NanoSight, UK). A Niton XL3 X-ray fluorescence spectrometer analyzer (Thermo Fischer Scientific, Germany) quantified heavy metal contents in the urine samples.Results Smokers had elevated UFP and cadmium content in urine compared with non-smokers (4.6 E8/mL and 20.6 ppm vs 3.4 E8/mL and 18.5 ppm, p=0.05 and p=0.05, respectively). Smokers had elevated levels of lead and rubidium compared with non-smokers (8.9 ppm and 27 ppm vs 7.8 ppm and 2 ppm, p=0.05 and p=0.04, respectively)Discussion We suggest that the trajectory of cadmium-related UFP in smokers begins by its inhalation into the airways. The UFPs induce inflammation and oxidative stress in the small airways, are subsequently translocated from the interstitium to the circulation and are finally detected and secreted in urine